The crystal structure of magnesian halotrichite, (Fe,Mg)Al2(SO4)4·22H2O: hydrogen bonding, geometrical parameters and structural complexity - Zhitova,E.S.; Sheveleva,R.M.; Zolotarev,A.A.; Krivovichev,S.V.; Shilovskikh,V.V.; Nuzhdaev,A.A.; Nazarova,M.A. (Journal of Geosciences, 2023)
The crystal structure of magnesian halotrichite has been refined for two samples collected as white efflorescences from the surface of geothermal fields associated with the Koshelevsky (sample VK4-09) and Centralny Semyachik (sample SC2-20) volcanos (both Kamchatka peninsula, Russia). Halotrichite and its Mg-rich varieties are common products of the acid leaching of rocks, both volcanic and technogenic. The crystal structures of two halotrichite crystals were refined in the P21/n space group (vs. P21/c used previously) with the unit-cell parameters a = 6.1947(2)/ 6.1963(5) Å, b = 24.2966(8)/ 24.2821(14) Å, c = 21.0593(8)/ 21.063(2) Å, β = 96.512(4)/ 96.563(9) °, V = 3149.2(2)/ 3148.3(5) Å3, Z = 4 to R1 = 0.055 and 0.067 for 5673 and 3936 reflections with I > 2σI reflections, respectively. The crystal structure consists of isolated Al(H2O)6 octahedra, SO4 tetrahedra, H2O molecules and [X(SO4)(H2O)5]0 clusters (X = Fe, Mg). The chemical analyses of both samples show their enrichment of Mg at the Fe2+ site. The analysis of geometrical parameters of the crystal structures of halotrichite and its Mg-analogue pickeringite suggests that the localization of O atoms carried out in this work is more accurate and the single-crystal X-ray diffraction data for the first time allowed localization of hydrogen atom positions. The refined number of H2O molecules agrees with the ideal chemical formula. The crystal structure complexity of halotrichite is estimated as IG,total = 2305 bits/cell, which belongs to the family of very complex mineral structures. The contribution of hydrogen bonding system plays a significant role in the overall bonding scheme and the overall complexity of the crystal structure, increasing the Shannon information amount more than twice from IG,total(noH) = 988 bits/cell (no hydrogen atoms) to IG,total = 2305 bits/cell (all atoms including hydrogen). The comparative distribution of halotrichite relative to other Fe-Al hydrated sulfates from the standpoint of structural complexity is considered.
Keywords: halotrichite; pickeringite; crystal structure; sulfate; hot spring; structural complexity